Blunt Abdominal Trauma in Children Problems and Solutions (Springer Singapore, 2018)
This book covers the epidemiology, mechanism, risk, various types of injuries, and practical approaches to treating children who have sustained blunt abdominal trauma. It includes dedicated chapters on each key aspect of pediatric blunt abdominal injuries, and explains in detail primary resuscitation and ancillary care for pediatric abdominal trauma. A separate chapter on imaging and interventional imaging helps pediatric caregivers select the right modality in the management of these patients. In addition, the book covers the management of hollow viscus injury and solid organ injury following blunt abdominal trauma. The content is supplemented with detailed flowcharts wherever required to help familiarize readers with the indications and to assist them in surgical decision-making. The book offers a valuable guide for practicing pediatric surgeons, residents in pediatric surgery and trauma surgeons, as well as for general surgeons, general surgery residents, practicing pediatricians and general physicians.